The translation process and different techniques used to translate documents in a high-quality way - Escobar González, Carlos Ernesto; López Mancía, Xenia Lilibeth; Mejía López, Aracely; Larin Montes, Daniel Alberto (Universidad de El Salvador. Facultad de Ciencias y Humanidades, 2025)
Disponible en soporte impreso